Paleoecología del Alto Guayacan Formación Uscari Mioceno provincia de Limón, Costa Rica - Aguilar, Teresita (2011)
A paleoecological analysys o fossils belonging to Uscari Formation (Miocene-Pliocene] at the Limón Province, Costa Rica is presented, Mollusk, foraminifers, arthopods, shark teeth, ichnofossil and plants led to the conclussion that litoral  to infralitoral enviroment was developed in that area with dense communities of suspension feeders and deposit feeders. That association shows characteristics of "Skolitos Ichnofacies" and "Vital lipostrate biofacies".